Pengaruh Penghindaran Pajak Terhadap Penerimaan Negara: Studi Kasus Pada Perusahaan Manufaktur di Indonesia - Felgi Kiko Fananta; Hadri Mulya (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The purpose of this study is to examine the effect of tax avoidance on state revenue with affiliated transactions as a moderating variable. Affiliate transactions are proxied by affiliate sales transactions, affiliate purchases and affiliate loans. This research method is a quantitative approach that is causal associative. The sample of this study is the financial statements of all manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2021. The data analysis technique is panel data linear regression with the help of Eviews 12 software. The results showed that tax avoidance has a positive and significant effect on state revenue; affiliate sales transactions do not moderate the relationship between tax avoidance and state revenue; affiliate purchase transactions do not moderate the relationship between tax avoidance and state revenue and affiliate loan transactions do not moderate the relationship between tax avoidance and state revenue. The results of this study as an illustration for the state how tax avoidance can affect state revenue so that it can be a reference material in making new rules in the future.